2022
DOI: 10.1039/d2ta05528g
|View full text |Cite
|
Sign up to set email alerts
|

A polyamino acid with zincophilic chains enabling high-performance Zn anodes

Abstract: Aqueous zinc metal battery (AZMB) has been regarded as a potential candidate of lithium-ion batteries by virtue of its high energy, low cost, and high safety. However, the practical application...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…These results show that triazole is involved in the coordination or adsorb process with Zn 2+ . [ 69 ]…”
Section: Resultsmentioning
confidence: 99%
“…These results show that triazole is involved in the coordination or adsorb process with Zn 2+ . [ 69 ]…”
Section: Resultsmentioning
confidence: 99%
“…These polar groups have good affinity for Zn 2+ ions, thereby inducing uniform nucleation. [163][164][165][166][167] Additives also can restrict the movement of water molecules by forming hydrogen bonds to protect the anode from being reached by water and inhibit the activity of water. [168] The use of a small amount of Et 2 O as an additive could be able to suppress the formation of dendrites on the anode during cycling (Figure 10f).…”
Section: Electrolyte Optimizationmentioning
confidence: 99%
“…Polyamino acids (PAA) were used as multifunctional electrolyte additives for modified zinc anode. The DFT calculations have showed that PAA has a unique long-chain structure, abundant nitrogen and oxygen functional groups and highly zincophilicity through preferential absorption by Wang et al [71] As a result, PAA can be tightly adsorbed on the surface of the Zn anode to construct a hydrophilic artificial coating. Four models were developed to study the interaction between the Zn foil and other components of the electrolyte, including PAA, AA, H 2 O and Zn ions.…”
Section: Adsorption Of Zincophilic Additives On the Surface Of Anodementioning
confidence: 99%